Lateral diffusivity from tracer release experiments in the tropical North Atlantic thermocline. Issue 5 (30th May 2013) - Banyte, Donata; Visbeck, Martin; Tanhua, Toste; Fischer, Tim; Krahmann, Gerd; Karstensen, Johannes
Abstract : [1] Lateral diffusivity is computed from a tracer release experiment in the northeastern tropical Atlantic thermocline. The uncertainties of the estimates are inferred from a synthetic particle release using a high‐resolution ocean circulation model. The main method employed to compute zonal and meridional components of lateral diffusivity is the growth of the second moment of a cloud of tracer. The application of an areal comparison method for estimating tracer‐based diffusivity in the field experiments is also discussed. The best estimate of meridional eddy diffusivity in the Guinea Upwelling region at about 300 m depth is estimated to be K y = 500   ±   200 m 2 s −1 . The zonal component of lateral diffusivity is estimated to be K x = 1200   ±   600 m 2 s −1, while areal comparison method yields areal equivalent zonal diffusivity component of K x e = 1000   ±   500 m 2 s −1 . In comparison to Ky, Kx is about twice larger, resulting from the tracer patch stretching by zonal jets. Employed conceptual jet model indicates that zonal jet velocities of about 0.015   ±   0.005 m s −1 are required to explain the enhancement of the zonal eddy diffusivity component. Finally, different sampling strategies are tested on synthetic tracer release experiments. They indicate that the best sampling strategy is a sparse regular sampling grid covering most of the tracer patch. Key Points: Meridional eddy diffusivity is found to be about 500 m2/s Zonal eddy diffusivity is found to be about 1200 m2/s Optimal tracer patch sampling strategies are reviewed